Proteomic characterization and antifungal activity of potato tuber proteins isolated from starch production waste under different temperature regimes - Bártová, Veronika; Bárta, Jan; Vlačihová, Andrea; Šedo, Ondřej; Zdráhal, Zbyněk; Konečná, Hana; Stupková, Adéla; Švajner, Josef (Applied microbiology and biotechnology, 2018)
Proteins were obtained from effluent of a starch manufacture by using different isolation temperatures (40, 60, 80, and 100 °C). The proteins, remaining in effluent after treatment of potato juice at 80 and 100 °C differed significantly in composition and in structural stability as well as in trypsin inhibitory and antifungal activities in comparison with the variants of 40 and 60 °C. The protein samples of 80 °C exhibited the highest antifungal activity and its average value of IC50 against five strains of two Fusarium species was determined in average at 0.18 mg ml-1. The 80 °C protein samples consisted predominantly of low-molecular proteins (7-17 kDa) identified as potato tuber protease inhibitors I and II. Predominantly, protease inhibitors II were identified for the protein samples obtained by 100 °C and here we identified 7 spots in comparison with 12 identified for the 80 °C samples. Samples of 40 and 60 °C with low antifungal activities represent high variability of detected and identified proteins. We identified various representatives of aspartic, cysteine, and serine protease inhibitors in both types of samples. These samples also contained Kunitz-type protease inhibitors that were not found in the 80 and 100 °C samples which documented thermal unstableness of Kunitz-type protease inhibitors. Functional stability at high temperatures and antifungal activity of isolated potato protease inhibitors I and II support the potential of this fraction usage in food, feed, pharmaceutical, or agricultural industry and offer new products for starch manufactures. At the same time, utilization of the stable protein fraction of waste deproteinized potato water promotes exploitation of potato starch production resources.
Keywords: Plant Tubers; rostlinné proteiny; mikrobiální testy citlivosti; hlízy rostlin; 2D gelová elektroforéza; Starch; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Proteomics; Protein Stability; stabilita proteinů; škrob; Electrophoresis, Gel, Two-Dimensional; tandemová hmotnostní spektrometrie; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Microbial Sensitivity Tests; Tandem Mass Spectrometry; Fusarium; Solanum tuberosum; proteomika; antifungální látky; Antifungal Agents; Temperature; Plant Proteins; teplota